Evaluation and Management of Patients with Hematoma After Gynecologic and Obstetric Surgery - Bekir Kahveci; Mehmet Obut; Serhat Ege; Mete Sucu; Nurullah Peker; Osman Uzundere; Gaye Kahveci; Mehmet Sukru Budak (Gynecology Obstetrics & Reproductive Medicine)
Objective: Postoperative hematoma following abdominal surgery is relatively rare and mainly depends on the type of surgery. Specific treatment including surgery or interventional radiology is sometimes necessary. The aim of this study is to evaluate the cases of postoperative hematoma after gynecologic and obstetric surgery.